Children’s environmental health: a target for all Pediatricians - Mennini, Maurizio; Valentini, Diletta; Di Camillo, Chiara; Vittucci, Anna Chiara; Krzysztofiak, Andrzej; Villani, Alberto (Progress in Nutrition, 2016)
Methemoglobinemia is caused by a congenital or acquired increase of methemoglobin (MetHb). A 11-months-old child came for episodes of peripheral cyanosis. The only altered exam was MetHb level, but non-pathogenic homozygous mutation of cytochrome B5-reductase gene. Our patient had begun to show cyanosis since the assumption of vegetable broth. Our case report is a warning to investigate the children’s environmental conditions.